2022
DOI: 10.1007/s10098-022-02345-7
|View full text |Cite
|
Sign up to set email alerts
|

Public perception of transitioning to a low-carbon nation: a Malaysian scenario

Abstract: Efforts such as the Glasgow United Nations Climate Change Conference of the Parties 26, the Paris Agreement (Paris agreement, United Nations, Paris, 2015) and the United Nations Sustainable Development Goals are supporting the drive to protect the planet from global warming by ensuring sustainable development. The oil and gas industry, as key contributor to greenhouse gas emissions, must transition to more sustainable energy solutions and play their part in reducing these emissions. Currently, oil and gas comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Furthermore, because they use less energy and have lower operating costs, energy-efficient devices frequently save money. Transportation initiatives in Saudi Arabia support the country's commitment to environmental sustainability and are in line with international efforts to move toward a low-carbon economy by placing a priority on the adoption of energy-efficient clean technologies [66]. This component demonstrates the understanding of how technology can create positive environmental change and guarantee a more sustainable transportation industry.…”
Section: Minimize Pollution and Environmental Impacts (Rii = 0709)mentioning
confidence: 83%
“…Furthermore, because they use less energy and have lower operating costs, energy-efficient devices frequently save money. Transportation initiatives in Saudi Arabia support the country's commitment to environmental sustainability and are in line with international efforts to move toward a low-carbon economy by placing a priority on the adoption of energy-efficient clean technologies [66]. This component demonstrates the understanding of how technology can create positive environmental change and guarantee a more sustainable transportation industry.…”
Section: Minimize Pollution and Environmental Impacts (Rii = 0709)mentioning
confidence: 83%
“…The third group of studies focused on the energy sector, analyzing operating sustainability reporting practices [35,39,[41][42][43]46,50,53], or the role of Sustainable Open Innovation [72] or decarbonization practices [65][66][67]. Several studies evidenced the difficulties in adopting sustainability projects and practices [59,75] and the central role of credit rating agencies [56] or stakeholders [95,98,99] in the energy sector.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, some scholars [64] investigating whether shareholders reward utility companies that have carbon-neutral goals with enhanced premiums, expressed through higher priceto-earnings multiples, found that there is no statistically significant enhanced premium in stock valuation. Recent research found that de-carbonization can contrast financial problems and favor social justice [65,66]. An in-depth analysis of a multinational energy and services company [67] showed the crucial role utility companies play in the transition to a carbon-neutral economy.…”
Section: Sustainability Practices and Financial Issuesmentioning
confidence: 99%
“…The results of this study showed that the average removal rate for combustible components might reach 88.47%, indicating great advantages and stability compared with normal calorific value coal gangue. Wong et al [22] presented a study of Malaysian companies to understand their perceptions towards a net-zero carbon future. Results indicated that, by implementing advanced technologies coupled with naturebased solutions, the employees as well as the company had the capabilities and showed a positive attitude toward using their financial resources to transition Malaysia into a carbon-neutral nation.…”
Section: Waste and Carbon Capturementioning
confidence: 99%